Effects of different routes of vaccination against Streptococcus agalactiae in red hybrid tilapia fingerlings (Oreochromissp.) - Aminuddin, 'Aisyah (2016)
Streptococcosis is a disease that develops following infection by Streptococcus sp. It is a major problem for fish production worldwide, and it is associated with high economic losses. This study was aimed at investigating the effects of different vaccination route against Streptococcus agalatiae in Red hybrid tilapia fingerlings. Ninety fingerlings were randomly divided into three groups, 1, 2 and 3 of 30 each. Two formalin-killed vaccine formulations were developed, feed based and spray. Group 1 was vaccinated using spray vaccine for 3 consecutive days in the 1st week and a booster dose for 3 consecutive days in the 3rd week. Group 2 was vaccinated once by using spray vaccine followed by a booster dose using the feed-based vaccine. While Group 3 served as a control group without any vaccination. All groups were challenged with 100 μL of S. agalactiae(109 CFU/mL) intraperitoneally. Following challenge, the fingerlings were observed for any clinical signs and mortality. Mucus samples of five fish from each group at sampling time were collected by using sterile swab at the surface of the skin. Gut lavage fluid was also collected, and both samples were subjected to indirect enzyme-linked immunosorbent assay (ELISA) to determine the IgM antibody levels against S. agalactiae. The results showed that the IgM antibody response in mucus and gut lavage fluids produced by the tilapia immunized with vaccination were not significantly different with each other even though different routes of vaccination were used.